Phenolic acids variability and grain quality of organically and conventionally fertilised old wheats under a warm climate. (29th April 2019) - Fares, Clara; Menga, Valeria; Codianni, Pasquale; Russo, Mario; Perrone, Domenico; Suriano, Serafino; Savino, Michele; Rascio, Agata
Abstract: BACKGROUND: We investigated three old wheats ( Triticum dicoccum, Triticum durum, Triticum spelta ) for effects of organic and conventional cultivation under equivalent nitrogen fertilisation (100 kg ha −1 ) on antioxidant content and composition, and on quality traits. RESULTS: Compared to conventional cultivation, organic cultivation had positive effects on test weight, while grain quality traits of protein content, gluten content and sodium dodecyl sulphate microsedimentation volume were 19.2%, 9.3% and 22.7% lower, respectively. Despite lower protein content with organic cultivation, this was still high (147 g kg −1 ); thus with adequate organic nitrogen fertilisation, the quality traits related to the technological properties of flour were maintained. Total phenolic content (TPC) was significantly higher for organic versus conventional cultivation, although free and bound phenolic acids were not significantly different. With discriminant analysis, only durum wheat differentiated the qualitative and compositional traits according to cultivation system. Separation of organic versus conventional cultivation in durum wheat and emmer was strongly affected by antioxidants (antioxidant capacity, TPC, yellow pigment content), dietary fibre, protein content and test weight. CONCLUSIONS: With adequate organic nitrogen fertilisation, protein and gluten contents remain high enough for good quality pasta. However, except for TPC, organic cultivation did not affect phenolic acids profile and antioxidant activity. © 2019 Society of Chemical Industry